Spatial and Temporal Variability of Winter Rainfall in Nepal - Bagale, Damodar (Himalayan Biodiversity, 2025)
The study analyzed time-series rainfall data from 107 weather stations in Nepal between 1977 and 2018. Rainfall variability ranged from 10.66 mm in the dry winter of 2006 to 133.51 mm in the wet winter of 1989. There were notable dry periods, such as in 2008-9 and 2016- 2018. The western region received more rainfall in the early decades, while the eastern Terai experienced drier conditions in recent decades. Decadal analysis revealed decreased winter rainfall across Nepal, with diverse patterns across regions. The composite analysis identified the dry and wet regions in large excess and large dry years. The central and eastern mountainous areas observed more rainfall, contrasting with the minimal rainfall in the lowlands of the eastern regions. These findings highlight changing climate dynamics, with regional variations in rainfall patterns across Nepal’s western, central, and eastern (WCE) regions.